O conceito hegeliano de experiência filosófica - Orsini, Federico (Revista Eletrônica Estudos Hegelianos, 2016)
Abstract: The present work purports to show the broadness of Hegel’s concept of experience, insofar as it cannot be reduced either to the perceptual experience or to the phenomenological experience of the subversion of the certainties of the ordinary consciousness. Beyond the phenomenological conception displayed by the Jena work, the most advanced phase of the system (understood as the unity of logic and philosophy of reality) presents an original articulation of objective thinking, within which philosophy itself plays the role of an experience of truth made by means of a specific way of thinking, namely, the way of scientific or conceptual thinking. In order to reconstruct this conception of philosophy, I will proceed in three steps. In the first place, I will clarify the sense in which Hegel’s conception of experience should be called ‘idealist.’ In the second place, I will show that, in the encyclopedic presentation of the system, ‘reflective thinking’ (Nachdenken) is the verb Hegel uses to designate (i) the elevation of common consciousness up to the scientific consciousness, (ii) the peculiar way of thinking that pertains to philosophy as science in the most rigorous sense: not a mere knowledge over the absolute, but rather absolute’s knowledge of itself. In the third place, I will highlight the polysemic conception of experience in Hegel’s thought and I will point out some virtuous circularities envolved in an adequate treatment of Nachdenken.